More Similarities than Differences - Kathy Crooks (Rural Nurse Organization; Binghamton University, 2005)
Bushy (2000) points out that "nursing practice in rural environments are very similar in Canada, the United States, and Australia" (p. 236). I think we can now add Japan to that list of countries in which rural nursing has similar characteristics. I recently returned from the island of Honshu in Japan and had the good fortune to meet and discuss rural nursing with a large group of nurses who work at the nursing school attached to Jichi Medical School. They recently received a mandate from the Japanese government to create the Academy of Rural and Remote Nursing at Jichi and are planning on becoming involved in the ICN rural and remote network that is being established. If you are anything like me, before I went to Japan I found it hard to believe that there would even be areas that are considered rural let alone remote in a country as densely populated as Japan. Much to my surprise I found out that because much of the country is very mountainous there are communities that are as isolated as any remote area in Canada. Interestingly, many of these locations have a similar demographic structure to areas in rural Canada, with the majority of residents being either very young or very old. It never ceases to amaze me that despite language differences, cultural differences and differences in health care systems that rural nurses from various parts of the world have so much in common. During my stay in Japan I was asked to be part of a panel discussion with nurses who work in a variety of rural areas throughout the country. I heard stories about lack of anonymity and familiarity in the community, something that could have happened anywhere in a rural community in Canada. I must say that this identification with other rural nurses regardless of culture or language bodes well for the establishment of an international network that will foster the sharing of ideas and concerns. I also think that it is comforting to know there will be a network of like-minded individuals that share many of the concerns and issues of nurses working in isolation, so ultimately no rural nurses need to feel that they are alone.